Insight into heavy metals (Cr and Pb) complexation by dissolved organic matters from biochar: Impact of zero-valent iron - Jia, Lixia; Wu, Weizhong; Jian Zhang; Wu, Haiming (SCIENCE OF THE TOTAL ENVIRONMENT, 2021)
In this study, batch experiments were conducted to investigate the immobilization of HMs (Cr and Pb) by DOM derived from biochar in the presence and absence of zero-valent iron (Fe) in nitrate and HMs co-contaminated groundwater. Both Cr and Pb were removed effectively in biochar-Fe aqueous systems, while only Pb could be mitigated in biochar systems. Excitation-emission spectrophotometry combined with parallel factor analysis (EEM-PARAFAC) revealed that DOM released from biochar mainly contained human-like and tryptophan-like substances. Moreover, the fluorescence of hemic-like components could be quenched differently by the complexation of HMs, which proved the different removal efficiencies of Cr and Pb in biochar aqueous phase. In biocharFe aqueous systems, Fe-C micro-electrolysis was formed in prior to the complexation of DOM-Fe hydroxides. Thus, the chemical reduction was the primary way to removal HMs in batch-Fe systems, which was corresponding with the less variation of DOM components when adding Cr and Pb into aqueous systems. Besides, the observed DOM components with higher aromaticity and humification after adding Cr and Pb, further indicated the complexation of DOM-HMs through the analysis of adsorption and fluorescence indices. These results will provide new insights into the HMs retention on biochar, particularly for the role of Fe on the complexation process. (c) 2021 Elsevier B.V. All rights reserved.